THE PRAGMATIC ASPECTS OF BORROWINGS - Mahmudova, Zilola (Журнал иностранных языков и лингвистики, 2023)
This article is dedicated to the pragmatic aspects of borrowings, semantic peculiarities and functions of loanwords. This article explores the notion of pragmatic borrowing, that is, incorporation of pragmatic and discourse features of a source language into a recipient language.